2019
DOI: 10.1002/2211-5463.12608
|View full text |Cite
|
Sign up to set email alerts
|

Autotaxin is a novel target of microRNA‐101‐3p

Abstract: Autotaxin (ATX), a vital enzyme that generates lysophosphatidic acid (LPA), affects many biological processes, including tumorigenesis, via the ATX–LPA axis. In this study, we demonstrate that microRNA‐101‐3p (miR‐101‐3p), a well‐known tumor suppressor, downregulates ATX expression at the posttranscriptional level. We found that miR‐101‐3p inhibits ATX regulation by directly targeting a conserved sequence in the ATX mRNA 3′UTR. Moreover, we observed an inverse correlation between ATX and miR‐101‐3p levels in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…It is found that the RNA-binding proteins HuR and AUF1 directly bind to the ATX mRNA 3’-UTR and influence ATX mRNA stability in Colo320 human colon cancer cells and LPS-stimulated THP-1 human monocytic cells [ 31 ]. microRNA-101-3p (miR-101-3p), a well-known tumor suppressor, inhibits ATX regulation by directly targeting a conserved sequence in the ATX mRNA 3’-UTR [ 32 ]. Recently, we clarified that the RNA methyltransferase NSUN2 could methylate the 3’-UTR of ATX mRNA at cytosine 2756.…”
Section: Mechanisms Of Atx Expression Regulationmentioning
confidence: 99%
“…It is found that the RNA-binding proteins HuR and AUF1 directly bind to the ATX mRNA 3’-UTR and influence ATX mRNA stability in Colo320 human colon cancer cells and LPS-stimulated THP-1 human monocytic cells [ 31 ]. microRNA-101-3p (miR-101-3p), a well-known tumor suppressor, inhibits ATX regulation by directly targeting a conserved sequence in the ATX mRNA 3’-UTR [ 32 ]. Recently, we clarified that the RNA methyltransferase NSUN2 could methylate the 3’-UTR of ATX mRNA at cytosine 2756.…”
Section: Mechanisms Of Atx Expression Regulationmentioning
confidence: 99%
“…A particularly interesting element in this report was the authors’ demonstration that miR-101-3p out-performed the ability of targeted siRNA against autotaxin to inhibit cell growth/confluence. Since only exogenous miR-101-3p addition was able to inhibit this effect <50%, it shows a more effective outcome using miRNA over siRNA, at least in this example [86].…”
Section: Mirna As a Puppet Master Of Lysophosphatidic Acid Signalimentioning
confidence: 99%
“…However, it remains to be explored whether modulation of ATX expression is involved in the physiologic and metabolic actions of these miRNAs. A TargetScan screen followed by testing in cancer cells also revealed that miR-101-3p inhibits ATX expression by directly targeting a conserved sequence in the ATX mRNA 3 UTR [71]. It is possible that miR-101-3p mediated ATX regulation also contributes to altered ATX levels during obesity and insulin resistance.…”
Section: Regulation Of Atx and Lpp3 In The Context Of Obesity And Metabolic Diseasementioning
confidence: 99%